QUR'ANI MORAL LEARNING METHODS IN SOCIETY - Shopiyah, Siti (Ridwan Institute, 2024)
This research aims to identify the Qur'anic moral learning method applied in the community and analyze its effectiveness in shaping the character of students. This study uses a qualitative descriptive approach to provide an in-depth overview of the diversity of learning methods, their effectiveness, and their application in the social context of the community. Data were collected through in-depth interviews, participatory observations, and documentation studies of various formal and non-formal educational institutions. The results of the study show that the habituation and exemplary methods are effective in building students' character through real examples, while the ibrah-mauizhah and amtsal methods provide a deep understanding of Qur'ani values. The discussion and storytelling method creates interactive learning and encourages active student engagement. This study also emphasizes the importance of integrating learning methods with community activities to increase the relevance and impact of learning. The diversity of methods found reflects the flexibility of Islamic teachings in educating noble morals according to the social context. This study recommends the use of a combination of methods to create varied, integrative, and relevant learning, so that Qur'ani values can be well embedded in students' lives. The results of the research are expected to be a reference for educators, community leaders, and educational institutions in developing more effective and applicable learning strategies.